Early and midterm results of minimally invasive aortic and mitral valve surgery via right mini‐thoracotomy. Issue 1 (6th November 2019) - Nakayama, Taisuke; Nakamura, Yoshitsugu; Kanamori, Kohei; Hirano, Takahisa; Kuroda, Miho; Nishijima, Shuhei; Ito, Yujiro; Tsuruta, Ryo; Hori, Takaki
Abstract: Objectives: There are few reports regarding minimally invasive aortic valve replacement concomitant with mitral valve surgery (MIAMVS). The aim of this study was to evaluate early and midterm MIAMVS results. Methods: We reviewed the medical records of 21 consecutive patients (nine females, 43%) who underwent MIAMVS through a right mini‐thoracotomy from December 2014 to April 2017. Mean patient age was 73 ± 7.4 years and four (19%) were New York Heart Association Class III or IV. Aortic stenosis and mitral valve insufficiency were the most common pathologies. All patients were followed for a mean period of 30 ± 8.5 months. Results: The types of surgery consisted of aortic valve replacement with mitral valve repair in 11 (52%) patients, and replacement of both aortic and mitral valves in 10 (48%), while a tricuspid valve repair, was performed in four. No conversion to a full sternotomy was necessary in any of the cases. Postoperatively, the median intensive care unit and hospital stays were 4.7 and 11.8 days, respectively, with no in‐hospital mortality. Following the initial treatment, all 21 patients were followed for a mean period of 30 ± 8.5 months (14‐45 months). All patients returned to NYHA Class I or II following the procedure. During the follow‐up period, there was no need for a heart valve reoperation for any of the patients and none showed recurrent mitral regurgitation (>mild), though one died from respiratory failure caused by pneumonia. Conclusions: MIAMVS can be performed via a right mini‐thoracotomy, with acceptable early and midterm results expected. This may be a feasible alternative to the standard median sternotomy approach.